PENGARUH UKURAN PERUSAHAAN, LEVERAGE DAN LIKUIDITAS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) - Cahyani, Marselina Dwi; Hariyono, Anwar (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2023)
This study aims to analyze the effect of company size, leverage and liquidity on the extent of disclosure of corporate social responsibility. The population used in this study are State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX) in the 2017-2021 period. The sample selection used a purposive sampling method according to the criteria determined by the researcher. The analytical method used is quantitative analysis with multiple linear regression tests. The results of the study show that company size can have a significant positive effect on CSR disclosure. While the results of the leverage and liquidity variable tests cannot have an effect on CSR disclosure. So that the first hypothesis is accepted while the second and third hypotheses are rejected.